THE USE OF DEIXIS IN GLADIATOR MOVIE MANUSCRIPT - Chuswatul Hasanah; Malikatul Laila; Aryati Prasetyarini (Universitas Muhammadiyah Surakarta, 2006)
This study is about the forms and references of deixis udes in